(untitled) (Fiep Bulletin - online, 2014)
Currently there is an invasion of modern sophisticated innovative technologies into the training practice, which should increase the effectiveness of training process. Agility training is included in them too. Modern concept of agility development includes open skills, where the fast change of direction of movement is carried out in the training conditions, which are not structured so much, and that is why they resemble the match conditions much more. In the work authors deal with the possibilities of development of agility in the conditions of soccer teams. The main research method is natural pedagogical experiment realized in two adult teams. Experimental stimulus, which is formed by specific and non-specific means focusing on agility development, is implemented in the training process of the experimental group (n=18) twice a week, while the reference group (n=9) went through a standard training process. For the measuring of the level of agility the standardized testing device Fitro Agility Check was used. Results were evaluated using Wilcoxon pair test. It was expected that under the impact of the 8-week-long agility training applied in the experimental group statistically significant changes will be recorded, while no statistic changes will be observed in the reference group. We also expected that right-legged players will record shorter reaction time in the item right-forward and left-legged players in the item left-forward. Results of the experiment did not prove the hypothesis because of no statistically significant improvements in agility level were found in the experimental group. Similarly, no significant changes were observed in the reference group. The hypothesis No. 2 that in players with the dominant right leg the shortest reaction times will be recorded in the item right-forward, while in the left-legged players the shortest reaction times will be recorded in the direction left-forward.Acknowledgements: This article was elaborated with the support of the grant scheme KE GA No. 029UKF -4/2011 Model Programmes of Activities Focusing on the Prevention and Remedy of Lifestyle Diseases in Adolescents